1998
DOI: 10.1128/iai.66.6.2486-2493.1998
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Protegrins against Yeast-Phase Candida albicans

Abstract: We used a two-stage radial diffusion assay to perform a structure-activity study of the antifungal effects of protegrin-1 (PG-1) on yeast-phase Candida albicans. While doing so, we computed MICs from the radial diffusion assay data by three methods and compared the respective values with results from colony count and broth microdilution assays. This allowed us to identify several technical modifications that improved the sensitivity and accuracy of radial diffusion assays. We found that both PG-1 and enantiome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(31 citation statements)
references
References 38 publications
3
28
0
Order By: Relevance
“…As a result, di‐K19Hc emerged as the most promising candidate for the development of a new antibiotic against antibiotic‐resistant bacteria. As in the case of many other peptides, including cecropin [29], magainin II [30], and protegrin [31], all of which exhibited antifungal and antibacterial effects, di‐K19Hc was also anticipated to exhibit antifungal properties. Hence, in this study, we have assessed the activity of di‐K19Hc against a panel of fungi, in a series of assays that were conducted in accordance with NCCLS procedures.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, di‐K19Hc emerged as the most promising candidate for the development of a new antibiotic against antibiotic‐resistant bacteria. As in the case of many other peptides, including cecropin [29], magainin II [30], and protegrin [31], all of which exhibited antifungal and antibacterial effects, di‐K19Hc was also anticipated to exhibit antifungal properties. Hence, in this study, we have assessed the activity of di‐K19Hc against a panel of fungi, in a series of assays that were conducted in accordance with NCCLS procedures.…”
Section: Discussionmentioning
confidence: 99%
“…The diameters of the clear zones were measured to the nearest 0.1 mm, and were expressed in units after subtracting the well diameter, 3.2 mm (10 units = 1 mm). The principles of the radial diffusion assay (9,10) and when it may be preferable to National Committee for Clinical Laboratory Standards (NCCLS) microbroth dilution assays for studying cationic peptides (11).…”
Section: Methodsmentioning
confidence: 99%
“…However, this rigid structure, in naturally occurring forms, prevents PG to undergo significant conformational changes upon association with membranes or upon oligomerization and also accounts for higher toxicity against eukaryotic cells (Ostberg and Kaznessis, 2005). In contrast to defensins, disulphide bond in PG is necessary for their antimicrobial activity, removing them decreases the activity significantly or abolishes it totally (Tamamura et al, 1995;Qu et al, 1997;Cho et al, 1998b). Recently Wang et al, showed that disulphide in Ib-AMP1, a 20-residue β-sheet AMP found in the seeds of Impatiens balsamina, is responsible for the intracellular activity.…”
Section: β-Sheet Peptidesmentioning
confidence: 99%